(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: There is a clear association between ABO blood group status and levels of Von Willebrandfactor (vWF). Blood group O is related with lower expression of vWF which leads to relative bleeding tendency. Thus, relationships between Bleeding time (BT), Clotting time (CT) and blood groups are important in certain conditions like epistaxis, surgery,thrombosis etc.Aims and Objectives: i)To determine the blood group, of the students and to determine their relationship with BT and CT. Materials and Methods: Institution based cross-sectional observational study done in Departmentof Physiology, Tripura Medical College & Dr. BRAM Teaching Hospital. BT and CT were done by Duke’s Method and Capillary glass tube method respectively. Blood groups were determined on basis of presence or absence of agglutination. Qualitativedata was expressed in percentage and quantitative data in frequency, mean and standard deviations. Chisquare test was applied. P value of <0.05 was considered as statistically significant. Results: BT more than 4 minutes was found maximum in group O (78.5%) compared to other blood groups (p = 0.001 by Chi-square analysis). Clotting time > 6 minutes found to be maximum in blood group O (53. 8%).Gender wise distribution showed CT > 6minutes in 39% females as compared to 34 %males (p value: 0.5826). Conclusion: In our study, CT was > 6 minutes and BT was > 4 minutes’ maximum in number in blood group O. Gender-wise BT and CT were higher in females than males. Our study showed that O blood group females are prone to certain diseases like epistaxis bleeding etc.